Primary Ovarian Pregnancy Mimicking Abdominal Pregnancy (2015)
The objectives of this study were to emphasise that ectopic pregnancy (EP) can occasionally occur in rare sites such as the ovary, and to show that it may be difficult making the diagnosis clinically and radiologically. It also highlighted the benefit of early surgical intervention in reducing mortality and morbidity from this condition. The case was a 31‑year‑old nulliparous woman who presented with amenorrhoea of 20 weeks and a 2‑month history of lower abdominal pain. Radiological studies suggested abdominal pregnancy coexisting with uterine fibroids for which she had an exploratory laparotomy, which revealed a primary right ovarian pregnancy necessitating the performance of right ovariectomy. Locating the sites of EP may still pose a diagnostic challenge. Despite the benefits and reliability of ultrasound scanning, there will still be situations where the definitive diagnosis can only be confirmed at surgery.